Thermochemical hydrogen sensor based on chalcogenide nanowire arrays. (19th March 2015) - Kim, Seil; Lee, Young-In; Choi, Yo-Min; Lim, Hyo-Ryoung; Lim, Jae-Hong; Myung, Nosang V; Choa, Yong-Ho
Abstract: The hydrogen gas-sensing properties have been investigated of two types of thermochemical hydrogen (TCH) sensors composed of thermoelectric layers based on chalcogenide nanowire arrays and anodic aluminum oxide (AAO) templates. The monomorphic-type TCH sensor, which had only Bi2 Te3 nanowire arrays, showed an output signal of 23.7 μ V in response to 5 vol% hydrogen gas at room temperature, whereas an output signal of 215 μ V was obtained from an n–p junction-type TCH sensor made of connected Bi2 Te3 and Sb2 Te3 nanowire arrays in an AAO template. Despite its small deposition area, the output signal of the n–p sensor was more than nine times that of the monomorphic sensor. This observation can be explained by the difference in electrical connections (parallel and serial conversions) in the TCH sensor between each type of nanowire array. Also, our n–p sensor had a wide detection range for hydrogen gas (from 400 ppm to 45 vol%) and a fast response time of 1.3 s at room temperature without requiring external power.